Urban design for small town regeneration: A socio-ecological approach - Hope-Bailie, Patrick (School of Architecture, Planning and Geomatics, 2023)
South Africa is a country with many small towns, each rich in heritage and culture and with their own unique spatial character. Unfortunately, most small towns are in distress. The focus of investment to bring about spatial transformation has typically been in either cities, or villages; i.e. urban or rural. However, Arndt, Davies and Thurlow (2018) suggest that a 3rd way would be to invest in secondary cities and small towns. Small towns are embedded in the cultural landscape, and sit at the intersection of rapid urbanisation and industrial agricultural practicetwo of the most significant features of the Anthropocene. The broad aim of this research is to explore potential solutions to the regeneration of small towns in South Africa. This research applies urban design thinking and practice in a rural context; using evidence-based design research and a socio-ecological approach. Urban design is a critical spatial practice to ensure there is a focus on urban form and structure, and the creation of positive, enabling environments. An approach that balances the social order with the ecological order produces a spatial structure that heals and repairs the whole. This is urban design, giving form to life.